THE GREAT WAR : And the Shaping of the 20th Century - Winter, Jay M., author 644576; Baggett, Blaine, author 644577 (New York, N.Y., USA : Penguin Studio, 1996)
The World War of 1914-1918, the Great War, was the first of the man-made disasters of the twentieth century. In many ways it was without precedent. Never had the battlefield been so vast, whether in the trenches, in the sky, or on and in the seas. Never had a war reached so deeply into the lives of people so far away from the battlefield. The shock waves generated by this cataclysmic event are felt to this day, as this dramatic narrative makes vividly clear. Here is presented a history of world war in a new way. The military flow of the conflict - from the invasion of Belgium in the summer of 1914 to the collapse of Germany in the autumn of 1918 - is followed throughout. But these epic events are rendered with fresh insights by the interweaving of the cultural history of the time - the hopes and dreams, the ideas and aspirations, the exhilaration and despair, both of those remote from power and of those who led them. This is a journey into the intense personal experiences of people trying to make sense of war on a scale the world had never seen. Like the acclaimed television series that it accompanies, The Great War pays special attention to the troubling aftermath of the war: the emergence of new nations amid old and festering problems; how the victims and survivors dealt with loss and disfigurement, guilt and hatred; and the terrible legacy of brutality that has marked so much of the twentieth century.